(untitled) (International Journal of Food and Nutritional Sciences, 2022)
COVID-19 or Corona virus is a new type of infection occurred first in December month of 2019 and is spreading to more than 180 nations including India. Government of India put the nation in a complete lockdown from March, 2020 and it is removed and re imposed based on severity of infection in different states across India. India begins its vaccination programme for Covid-19 on 16th January 2021 and it is now in third phase. The first phase of vaccination covers health and frontline workers and about 14 million frontline and healthcare workers are vaccinated that is less than as the target of 30 million. The second phase of vaccination programme covers all the people in above 60 years of age and, people between 45 and 60 years of age with one or few qualifying comorbidities, and frontline and healthcare workers do not get vaccination in first phase, The third phase of vaccination progrmme expands eligibility criteria to all people above 18 years of age and the Government of India allows higher flexibility for carrying out vaccination programme in third phase. India uses mainly Covishield and Covaxin vaccines and followed by Sputnik V and Moderna is approved for vaccination for Covid-19 in India. India adopts centralized procurement policy for vaccination for Covid-19 and as on date, the total vaccination administrated is 43,51,96, 001 in India as a free of cost. Now India is number one nation in vaccination for covid in the world. India has distributed over 58 million vaccine doses to 65 nations through vaccine friendship programme and India stops its commercial exports from March because of domestic needs of vaccines and the stoppage of exports will continue till December, 2021. India is planned to complete vaccination for Covid-19 to all by the end of December, 2021. India is planned to complete vaccination for Covid-19 to all by the end of December, 2021. Covishield, Covaxin and Sputnik V are highly effective against delta variant in India. The oxygen crisis is happing in India during second wave of Covid due to inadequacy of the supply chain and distribution networks of oxygen tankers to transport medical oxygen from producers to the hospitals not because of availability of medical oxygen in India. At present, India is having adequate amount of medical oxygen and it is highly ready to tackle any kind of medial oxygen related problems.